Integrating critical thinking in junior high school EFL classrooms: Teachers' perspectives and instructional practices - Jumariati, Jumariati; Yamin, Moh.; Sutiono, Cayandrawati (Journal on English as a Foreign Language, 2026)
EFL teachers’ knowledge, perceptions, and practices regarding integrating critical thinking (CT) in English language teaching are essential. However, research on this area shows conflicting results, particularly in Asian contexts. This study investigated EFL teachers’ perceptions and practices on integrating CT in their classrooms. Three EFL teachers of junior high schools in Banjarmasin, South Kalimantan, Indonesia, participated in the study. They were selected purposely based on teaching experience, professional teachers’ certification status, and participation in CT workshops. A qualitative phenomenological design was adopted through the use of semi-structured interviews and documentation on teachers’ lesson plans. A thematic analysis was used in the data analysis. Results showed that the teachers had a good understanding of CT and perceived its integration in EFL lessons positively. They incorporated CT through analyzing texts, evaluating characters, separating facts from opinions, drawing conclusions, making presentations, discussions, and writing paragraphs, which aligned with their lesson plans. The study also revealed that students’ English proficiency affected their ability to express ideas and explain reasons during CT activities. This study highlights the need for further research incorporating students’ views and utilizing classroom observations to verify the suitability between teachers’ perceptions and their teaching practices.